Pediatric emergency department organization and social care practices among U.S. fellowship programs. Issue 4 (11th August 2022) - Assaf, Raymen Rammy; Assaf, Ryan David; Barber Doucet, Hannah; Graff, Danielle
Abstract: Background: Social care has become increasingly relevant to the emergency physician and includes activities that address health‐related social risk and social needs. The literature has consistently documented substantial health care provider challenges in incorporating social care into routine practice. Yet, interventions on the health care organizational level hold promise to bring about more widespread, sustainable impact. Methods: This study was a subanalysis of the 2021 National Social Care Practices Survey data set among pediatric emergency medicine (PEM) program directors (PDs) and fellows. The purpose was to investigate the association between health care organizational factors and PEM physician social care practices and perceptions among PEM PDs and fellows. We performed binary and ordinal logistic regressions of organizational factors and five specific PEM physician social care perspective and practice outcomes. Results: The sample population included 153 physicians—44 PDs (49% response rate) and 109 fellows (28%). PDs and fellows with access to a social care systematic workflow in their pediatric emergency department (PED) had higher odds of comfort assessing social risk (odds ratio [OR] 2.1%, 95% confidence interval [CI] 1.1–4.0), valuation of social care (OR 3.2, 95% CI 1.3–7.9), preparedness to assist families (OR 2.4, 95% CI 1.1–5.2), screening tendency (OR 2.2, 95% CI 1.1–4.5), and ability to refer to community resources (OR 2.3, 95% CI 1.2–4.6). A similarly directed, but less pronounced pattern was noted with access to a community resource database for referrals and 24‐h access to a social worker in the PED. Conclusions: PED organizational factors—particularly access to a social care systematic workflow—appear positively associated with PEM physician practices and perceptions of social care delivery. Further research is under way to advance understanding of PEM training factors in social care.